Relationships between serum levels of lactate dehydrogenase and neurological outcomes of patients who underwent targeted temperature management after out-of-hospital cardiac arrest. Issue 24 (18th June 2021) - You, Yeon Ho; In, Yong Nam; Park, Jung Soo; Yoo, Insool; Kim, Seung Whan; Lee, Jinwoong; Ryu, Seung; Min, Jin Hong; Jeong, Won Joon; Cho, Yong Chul; Oh, Se Kwang; Ahn, Hong Joon; et al.
Abstract : Abstract: This study aimed to evaluate times for measuring serum lactate dehydrogenase levels (SLLs) to predict neurological prognosis among out-of-hospital cardiac arrest (OHCA) survivors. This retrospective study examined patients who experienced OHCA treated with targeted temperature management (TTM). The SLLs were evaluated at the return of spontaneous circulation (ROSC) and at 24, 48, and 72 hours later. Neurological outcomes after 3 months were evaluated for relationships with the SLL measurement times. A total of 95 comatose patients with OHCA were treated using TTM. Seventy three patients were considered eligible, including 31 patients (42%) who experienced good neurological outcomes. There were significant differences between the good and poor outcome groups at most time points ( P  < .001), except for ROSC ( P  = .06). The ROSC measurement had a lower area under the receiver operating characteristic curve (AUC: 0.631, 95% confidence interval [CI]: 0.502–0.761) than at 48 hours (AUC: 0.830, 95% CI: 0.736–0.924), at 24 hours (AUC: 0.786, 95% CI: 0.681–0.892), and at 72 hours (AUC: 0.821, 95% CI: 0.724–0.919). A higher SLL seemingly predicted poor neurological outcomes, with good prognostic values at 48 hours and 72 hours. Prospective studies should be conducted to confirm these results.